Children's Repetitive and Intermittent Sprinting Performance (CRISP) Test: A new field-based test for assessing anaerobic power and repeated sprint performance in children with developmental coordination disorder. (October 2019) - Smits-Engelsman, Bouwien C.M.; Bonney, Emmanuel
Highlights: The distance (6 × 30 m) used in the CRISP test appears to be suitable for inducing fatigue in children. Children with p-DCD performed poorer on all power and agility tests used in this study. Children with p-DCD did not fatigue more on the CRISP test compared to TD peers. Children's performance on anaerobic tests may be influenced by the coordinative task constraints embedded in those tests. Abstract: Background: Evidence on anaerobic power and sprinting performance of children with Developmental Coordination Disorder (DCD) is limited. Aims: The primary aim of this study was to investigate if the Children's Repetitive and Intermittent Sprinting Performance (CRISP) test could induce fatigue among participants. Secondly, the study examined the construct validity of the test in children with probable DCD (p-DCD) and typically developing (TD) peers. Methods and procedures: The study was carried out in two phases. In phase 1, we compared performance of 25 children (7–12 years) on the CRISP test to their performance on the Muscle Power Sprint test (MPST). For phase 2, forty-six (n = 46) participants with p-DCD were matched with TD children (n = 46) on age, weight and sex. Anaerobic performance of participants was assessed using the CRISP test, 10 × 5 m sprints straight and slalom tests, side jumps, stepping on platform task and the ladder agility test. Outcomes and results: Phase 1: The increase in running time on the CRISP test was greater than on the MPST, indicating that the CRISP test was more fatiguing than the MPST. Phase 2: Children with p-DCD had poorer anaerobic capacity (muscle power, muscle endurance) compared to their TD peers. However, fatigue was comparable between the two groups. The differences in performance between p-DCD and TD children were found to be greater for tests with more agility elements. Conclusions and implications: The findings showed that CRISP test could induce fatigue in children. The CRISP test was also found to have positive construct (i.e. known-group) validity. The differences in muscle power and endurance between children with p-DCD and TD peers tend to widen when assessments are performed with tests having high agility components.